Efeito do estradiol sobre o acúmulo lipídico em ratas. - Eva das Gracas Abeles (2007)
It is well established that ovarian hormones modulate the metabolism of adipose cells and present a protective effect against cardiovascular disease. This study evaluated the estradiols effects on adipose tissue metabolism of normotensive, Wistar-Kyoto (WK) and spontaneously-hypertensive rats (SHR). Twenty one days after ovariectomy (OVX) the rats received vehicle (0,1 mL oil/100 g bw) or estradiol (5g/0,1 mL/100 g bw). Following estradiol administration, a significant decrease of systolic arterial pressure in the SHR was observed. Our results show in both goups, that adipocytes isolated from estradiol treated animals were smaller than that isolated from the vehicle treated rats, and increase in the cell number was observed only in WK rats. The number of adipocytes from SHR was higher than WK, independently of treatment. Adipose tissue lipoprotein lipase activity increased after OVX in both groups, although in the SHR the values were 50% - 300% smaller than that observed in WK rats. Estradiol administration decreased the enzyme activity, independently of the group or treatment. The presence of insulin (2,5 ng/mL) in the incubation media, stimulated glucose uptake by periuterine and mesenteric adipocytes from WK and SHR groups. However, the effect was more evident in the estradiol treated rats. The replacement with estradiol significantly increased basal lipolysis in periuterine adipocytes from both groups. In relation to mesenteric adipocytes, the treatment with estradiol significantly increased basal lipolysis only in WK rats. The dose-response relationship for insulin inhibition of lipolysis demonstrated that mesenteric adipocytes from SHR treated with estradiol are considerably more sensitive to insulin inhibition of isoproterenol-stimulated lipolysis than those from WK animals. The lipolytic activity in the SHR was higher than that of WK independent of the treatment, suggesting an increased sensitivity to isoproterenol in relation to the WK rats. It was observed that in the periuterine tissue of WK treated with estradiol, a significant increase occurred in the expression levels of peroxisome proliferator activated receptor (PPAR), not observed in the mesenteric tissue. In the SHR it was observed a lower expression of PPAR in relation to the WK and differences of expression of this gene due to the treatment was not observed in periuterine tissue. However, in the mesenteric tissue, the levels of PPAR mRNA were higher than that of other sites and the treatment with estradiol significantly increased the expression levels of this gene. The treatment with estradiol significantly increased the expression of PPAR in the liver, of both groups. In the SHR the treatment with estradiol increased, in a significant way, the levels of PPAR also in the heart. The results presented in the present work suggest that the estradiol deficiency can increases the cardiovascular risk, through the increase in blood pressure, as shown in SHR. The reduction of sensitivity to insulin after OVX unchained problems such as the inability of the insulin to suppress lipolysis after stimulus by catecholamines. The reduction of sensitivity for insulin was also harmful to the glucose uptake after OVX. It was evidenced that, the administration of estradiol, through the increase of PPAR and PPAR expression increased the sensitivity for insulin. Visceral adipocytes are lipolyticaly more active than other depots, and the increase in glucose uptake, important for glycerol-3-phosphate production, may contribute to decrease fatty acids secretion by increasing esterification and consequently decreasing the flux of fatty acids to liver.